What is left of the Marxist interpretation of Darwin? (Culturas Científicas, 2018)
A familiar Marxian reading of Darwin’s theory of natural selection holds that the theory functioned to naturalize – and so legitimate – competitive power relations in Darwin’s industrial, capitalist, and imperialist Britain. This essay examines this reading in light of more recent studies of Darwinism and Marxism. One aim is to show that the luxuriantly rich account of the social embedding of Darwin’s science now available from historians of science, though indebted to the Marxian tradition in all sorts of ways, does not support the legitimation claim. Another aim is to go beyond that problematic claim in putting together a new account of how the Malthusian struggle for existence came, for socially explicable reasons, to have a central place in Darwin’s theory.
Keywords: Darwin; Marx; historiography; evolution; culture; victorian context